1997
DOI: 10.1097/00007632-199702150-00003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Evaluation of Cross-Link Designs in Rigid Pedicle Screw Systems

Abstract: The use of cross-linkage in spinal fusion increases torsional stiffness in pedicle screw and hook constructs. This study 1) confirmed the effectiveness of cross-linkage in limiting torsional motion and showed the superiority of two cross-links to one cross-link in limiting torsional motion, 2) showed that increase of torsional stiffness of a cross-linked construct is proportional to the cross-sectional area of the cross-link, and 3) demonstrated that cross-links do not increases stiffness in the lateral flexio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 9 publications
4
54
1
1
Order By: Relevance
“…After hemivertebra resection, compression is applied on the convex side to close the excision gap. Ideally, placement of pedicle screw 15°medially enhances the rotational stability [20]. However, unlike adult spine, young children's pedicle is tiny and often asymmetric in size, likely unable to withstand the significant compressive force.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After hemivertebra resection, compression is applied on the convex side to close the excision gap. Ideally, placement of pedicle screw 15°medially enhances the rotational stability [20]. However, unlike adult spine, young children's pedicle is tiny and often asymmetric in size, likely unable to withstand the significant compressive force.…”
Section: Discussionmentioning
confidence: 99%
“…Thus additional use of implants are proposed to support the pedicle-screw-based instrumentation, like additional rod connecting laminar hooks to facilitate closing the excision gap [28]. Based on previous biomechanical testing, the crosslink can improve the axial stability of the instrumentation [19][20][21][22]. Hence, we recommended using a crosslink as an alternative to enhance the stability of the total instrumentation in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,32,33 These studies have revealed that cross-linkage did not significantly increase the stiffness of posterior implants for compression/flexion motion. In the present study, the increase in stiffness of SS-Plate-B implants was 22.2% compared to the SS-SB variant (P Ͻ 0.001).…”
Section: Failure Mechanismsmentioning
confidence: 97%
“…Such extreme loading conditions may very well change the fixation stability under different compressive preloading situations. According to Brodke et al [37] and Dick et al [38], pedicle screw fixation with an added cross-link can improve stability in an axial rotation, but there is a negligible change in stiffness during lateral bending. Comparing the BPSR with the BPSR-CL for lateral bending and axial rotation, we noted similar results.…”
Section: Surgical Considerationsmentioning
confidence: 99%